Determinan Akuntabilitas dalam Pengelolaan Dana Desa - Kadek Noviani; I Gede Putu Banu Astawa (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
The purpose of this research is to explain the accountability that exists in the management of village funds in village administrations throughout Buleleng Regency with a population of 129 villages. The target sample is 61 villages taken through consideration of the purposive sampling technique. A quantitative approach was used in the study, with a questionnaire used as primary data and secondary data obtained through the Department of Community and Village Empowerment of Buleleng Regency. This study uses linear regression analysis with the help of SPSS 24.0 for Windows. From the tests conducted, it is known that the independent variables, namely the quality of human resources, compliance with accounting rules, and the use of village financial system applications show a positive influence on the accountability of village fund management. The results of the coefficient of determination show that 72.1% of village fund management accountability is influenced by the independent variables tested, while 27.9% is influenced by other independent variables.